PERCEPTIONS OF HEAD AND SCHOOL TEACHERS IN DEVELOPMENT AND MONITORING PROCESS OF PRIMARY EDUCATION IN KHYBER PAKHTUNKHWA PAKISTAN - Falak Naz; Dr. Shawana Fazal; Farrukh Nazir (International Journal of Contemporary Issues in Social Sciences, 2024)
In many developing countries, including Pakistan, achieving Universal Primary Education (UPE) remains a significant challenge. This study aimed to analyze the perceptions of head and school teachers to find the development and monitoring process of primary education in one of Pakistan’s provinces, Khyber Pakhtunkhwa (KP). The study surveyed 506 head and school teachers selected from five districts within KP, using a proportionate stratified random sampling technique. Data was collected through a self-developed questionnaire and analyzed using SPSS version 21. The findings indicate that both head and school teachers perceive that moral principles are instilled among primary school children. Moreover, the School Quality Management Initiative (SQMI) monitors the teaching and learning process, and non-government organizations (NGOs) participation is reducing illiteracy. They agree that efforts are being made to bring all children into school; however, they do not agree that school performance is improving due to the monitoring process. The Sustainable Development Goals (SDGs) are not fully implemented, and the standards are not being met. Therefore, enhancing the standards to ensure full compliance with SDG targets and improve overall school performance is recommended. Additionally, the support prioritized, and further research be conducted to identify the indicators of poor performance to strengthen primary schools, ensure all children are brought into the education system, and enhance the effectiveness of the SQMI and other monitoring processes in KP.